PENINGKATAN BELAJAR GERAK DASAR MELALUI PERMAINAN POS BERANGKAI PADA SISWA KELAS III SD N SURJO 02 TAHUN PELAJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
Research subjects in this study were fourth grade students of SD Negeri 2 Dermaji who are 32 studentsconsisting of 17 male students and female students of 15 students. The method used in this study is aclassroom action research, carried out in two cycles, the first cycle and second cycle. Cycle I is a directobservation at the time of learning by using the observation sheet with psychomotor tests passing downthe group. Meanwhile, a second cycle of action on psychomotor tests individually. Data collectiontechniques are technical tests carried out, in the form of skills tests, tests students' attitudes and cognitivetests.The research proves that the value of daily test results on the initial conditions is still relatively lowat 46.87% on aspects of psychomotor, cognitive aspects of 70.5% and 75.35% on the affective aspects ofthe sikuls I, after a game of netball action in group. Then in sikuls II, the value of daily test results hasincreased 90.62% on aspects of psychomotor, cognitive aspects of 87.20% and 93.50% on the affectiveaspects.Based on the analysis and discussion, it can be concluded that the Through Ball Game Nets canimprove learning outcomes On passing under the Fourth Grade Students of SD Negeri 2 Dermaji.